Developing a Wetlands-Based Monograph Book of English for Business Teaching and Learning Models - FADILA, Raisa; ARINI, Dini Noor; DEVIYANTI, Rafista (PT Keberlanjutan Strategis Indonesia, 2024)
Modern technological developments substantially impact many essential areas, including teaching English as a second language. Science and commercial advancements depend on the ability of specialists around the world to communicate using English. This motivates instructors to switch from teaching English in general to teaching English for Specific Purposes (ESP), which focuses on assisting students in achieving language proficiency. In Banjarmasin, Indonesia, vocational high schools provide English for Business as a division of ESP. Since no monograph book gives learning models for teachers on how to teach English in a way that is acceptable and engaging to students, challenges develop while teaching English in vocational schools, especially for students majoring in business. This research aims to produce a monograph on teaching models of English for Business due to the significance of meeting teaching and learning aims and the lack of suitable references for teaching English to business students in vocational high schools, especially in wetland areas. This study employs a research and development approach since it wants to create a product while considering requirements analysis. It is believed that the findings of this study would help teachers deliver effective and worthwhile instruction in wetland areas while also raising students' academic achievement.